How do financial institutions forecast sovereign spreads? - Jacopo Cimadomo; Peter Claeys; Marcos Poplawski Ribeiro (European Central Bank (ECB), 2014)
This paper assesses how financial market participants form their expectations about future government bond spreads. Using monthly survey forecasts for France, Italy and the UK between January 1993 and December 2011, we test whether respondents consider the expected evolution of the fiscal balance—and other economic fundamentals—as significant drivers of the expected bond yield differential over a benchmark German 10-year bond. Our main result is that a projected improvement of the fiscal outlook significantly reduces expected sovereign spreads. Overall, the findings suggest that credible fiscal plans affect expectations of market experts, reducing the pressure on sovereign bond markets.
Keywords: E62; G10; H30; 330; Consensus Economics Forecast; market expectations; sovereign bond spreads; survey data